Water Resource Management for Human Consumption in Costa Rica and Its Impact on Post-Neonatal Infant Mortality - Vega Araya, Edwin (2008)
If you are thinking of reducing child mortality, it is useful to divide mortality by the time that happens. Perinatal and neonatal mortality (in the first days of life to 27 days old) and post-neonatal mortality (between 28 and 365 days old). The present study concerns the latter period of death, the rate of post-neonatal infant mortality rate (IMR post-neonatal), which although has a lower relative weight, it’s really important. First we analyze the influence of other factors, including socio-demographic factors through the study of the relationship between the Social Development Index (IDS) and the post-neonatal TMI. Then identifying the entities that provide potable water service in different districts of the country, and, given their different characteristics, analyze and verify the assumption that the entity provider (or administrator) is a factor behind the change TMI of post-neonatal between districts. To reduce post-neonatal TMI needs working on the quality of drinking water. The first suggestion is that each district must have a clear and responsible supplier of drinking water. Judging by the success of ICAA and ESPH it seems more successful having managers based on local control (defined in terms of fares and quality control) from ARESEP and not by municipal councils that are more likely to delay such measures as placement of gauges, the execution of certain investments, and so on.